Leveraging AI Technology to Analyze the Impact of Customer Participation on Value Creation in Sustainable Systems - Reepu (EPJ Web of Conferences)
There are changes in technology and more information among consumers, which means that customers and companies are becoming more aggressive in working together. One of the changes that come with this shift is the value that people in the brand network create through their actions. Previous studies have mostly looked at the parts of customer resources that are used in the stages of creating value and realizing value. However, this study did not look at how customer involvement affects the building up of customer resources and value throughout the customer journey or how customer regulatory focus might affect these two factors. The resource theory point of view is used. A poll was given to 451 current customers in China who are part of well-known brand networks in order to look into the links between customer involvement, customer resources, and customer value. The SEM method was used for the work. The study also looks at how governmental attention affects the overall customer experience. It was found that human resources and customer relationship resources have a positive effect on customer interaction value and customer term value. As a result, human resources act as a go-between for the whole customer process, making sure that customers are engaged and getting value from the company.